Lean Office aplicado ao fluxo documental de uma Universidade Pública visando à adequação à Legislação - Boriolo, Raquel Ottani (Universidade Federal de São Carlos, 2018)
Document Management is a strategical activity in organization, because it provides a series of procedures which are related to its production, proceeding, use, assessment, and archiving of frequently or less frequently used documents, besides providing the correct destination for documents by eliminating those which do not have a historical value or collecting them, in case they have any value, therefore assuring their conservation. In public organizations, Document Management constitutes the process that can ensure law enforcement concerning documents protection and keeping, besides promoting archiving efficiency. However, according to the literature, Brazilian national archives have many problems in their document flow. Lean Office is an approach used for administrative processes, which helps at identifying and eliminating problems and waste, as well as streamlining and adding value to those activities. Thus, its applicability improves document flow in Brazilian national archives. The present research aimed at implementing Lean Office tools at the document flow by an administrative sector of a public university with the goal of optimizing the process and making it appropriate concerning the Document Management of the National Archives. The exploratory research was carried out at a public sector of the Federal University of São Carlos (UFSCar) and it has a qualitative approach as a basis for its development. The methodological procedures were bibliographical research, documental research and a case study. The Lean Office tool Value Stream Mapping has enabled the recognition of flow document activities which add value to the process and those which do not add value and, therefore, could be eliminated. It has also allowed the observation of flow inadequacies related to what is proposed by the National Archive. This research has identified that there were many problems because the activities in the sector were not guided by Document Management, such as the absence of a standard among the archiving teams in order to ease the search for a document in a current and intermediate archive by anyone; some documents do not have identification of the necessary information to have a destination after finishing the keeping deadline, so they could be eliminated or sent to the permanent file, resulting in document accumulation; some archives do not ensure document conservation, which can cause the loss of documents with historical value; the sectors do not have clear procedures and the teams are not trained. Other Lean Office tools were used in this research, such as: A3 report, assisted by the tool 5 Whys, analyzing the problems and inade0quecies origins; 5W1H to contribute with action proposition of countermeasures suggested at the A3 report and 5S to assist at planning the implementations of the action plan propositions. By using these tools, it was possible to present a future proposal, transforming or eliminating problems and inadequacies, which enabled the proposition of adequacy actions and streamlining processes, making them more effective and less expensive. It has also facilitated the creation of a document flow which is in accordance with Document Management. As a conclusion, Lean Office is able to improve document flow in public organizations and Lean Office tools can be applied to document flow, aiming at enhancing efficiency and adequacy to the rules of the National Archive concerning Document Management.
Keywords: Gestão documental; Fluxo documental; Arquivo nacional; Document management; Document flow; National archive; Lean office; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS